PROFIL OF THE DOUBLE LAYER FLOATING NET CAGE FISH CULTIVATION BUSINESS IN THE SAGULING RESERVOIR (CASE STUDY OF BONGAS VILLAGE, CILILIN DISTRICT, WEST BANDUNG REGENCY) - Gumilar, Iwang; Rasyid, Raffael Muhammad Sabili; Andriani, Yuli; Maulina, Ine (Universitas Mataram, 2025)
Fish raising using nets is part of intensive reservoir fish farming. This method is known as floating net cages or KJA in reservoirs. The purpose of this research is to examine the overall description of double-layer net KJA fisheries in Bongas Village, as well as the technical performance of these enterprises. The research was carried out in double-layer floating net cages at Saguling Reservoir. A case study research methodology was applied. Purposive sampling was utilized to obtain data from respondents who met the following criteria: fish farmers, active KJA cultivation, 5 years of business experience, and KJA owners/workers. The analysis employed was descriptive. According to the study's findings, there were 44,065 KJA plots and a total output volume of 27,824 tons. The population is in productive age, with 5337 people; the main occupation of respondents is KJA fish farmers, with 17 people (54.84%), business experience of more than 5 years; and in terms of technical performance, one KJA plot measures 7 m x 7 m, with a top net measuring 7 m x 7 m x 4 m. The second layer is 14 m x 14 m x 9 m, with the KJA located at a depth of 8 meters. The brightness of the KJA site is 0.45m, the pH concentration is 6-8, the current strength is 20-40 cm/s, and the fish species include tilapia, carp, and patin. Stocking density: 50-100 fish per m3. Feed 788 and S99. Treatment involves painting or purchasing new ones. Vitamins or antibiotics are given to fish to maintain their health. The water quality around the KJA is pretty excellent. The investment expenses vary from 25 million to 50 million. For operations, KJA owners engage one person to monitor up to ten KJA devices